Drawing of Tower
Drawing of Tower with writing at the bottom. The bottom reads "Study for tiling to tower of drain building for Mr. William Randalph apart san Simeon. Scale 1/2 inch, 1 foot. Julia Morgan architecture." There is an illegible date on the bottom left.